Silence and Self-expression in Charlotte Brontë’s Shirley: An Application of John Searle’s Speech Acts Theory - KHAZAI, Sara; S. Beyad, Maryam; R.G. SABBAGH, Mahmoud (Anafora, 2023)
Despite the “comedic” happy ending of Brontë’s Shirley (1849), its heroine’s taciturn incommunicativeness towards the end of the novel in contrast to her lively former derring-do, has naturally given rise to various speculations about the nature of her transformation. The fact that many of the final exchanges between her and Louis Moore are reported with a temporary shift of point of view in Louis’s personal journal, with an obvious artistic distance between the narrator’s voice and his, merely serves to cast darker shadows over the veracity of his conclusions. The present application of Searle’s speech acts theory to some dialogue samples from Shirley, focuses on the differences of communicational styles in its heroine at three stages of the narrative and concludes that feeling the weight of the “new world” she has entered after her betrothal, Shirley finds that there is a consequent need for her to employ more expressive speech acts to elucidate, fewer assertives for greater self-effacement, and more frequent hedges to give a softer edge to her directives. Shirley’s linguistic technique now relies for its success on her silence and tolerant manner rather than persuasive arguments, and her speech mannerisms might in fact be presumed a “performance.” She thus shifts her style of expression intentionally, and in such a fashion as to empower Louis further and hand the conversational reins over to him.